Parents' personality and parents' perceptions of the parent-child relationship as a predictor of social competence in young children. - Pillay, Levandri (My University, 2014)
Early childhood represents a critical period for the development of social skills and abilities that enhance social competence. One of the main aspects that contribute to this development is the parent-child relationship. The purpose of this study is to explore this area of the parent-child relationship by focusing on parenting personality and parents’ perceptions. The aim of this study was to investigate whether parents’ personality could influence the parent-child relationship and consequently predict social competence in young children. Parents’ personality related to the five personality dimensions as delineated by the Five Factor Model. Parents’ perceptions focused on Attachment, Discipline Practices, Involvement, Parenting Confidence, and Relational Frustration. The study consisted of 62 parents of children between the ages of three and six years old. Participants were asked to fill out three questionnaires, the Parenting Relationship Questionnaire for Pre-schoolers (PRQ-P), the Neuroticism Extraversion Openness-Five Factor Inventory (NEO-FFI), and the Social Competence Scale (SCS). The five personality dimensions were found to be significantly correlated with parenting perceptions of the parent-child relationship and the preschool child’s social competence. For example Neuroticism, Extraversion, Agreeableness and Conscientiousness were significantly related to Parenting Confidence, however only Neuroticism and Agreeableness correlated significantly with social competence in children. More specifically, Neuroticism was negatively related to Emotional Regulation and Agreeableness was positively related to Prosocial Behaviour. In addition to this regression analyses showed that the parent-child relationship, personality, and social competence were strongly mediated especially with regards to Neuroticism, Parenting Confidence as well as Relational Frustration and Emotional Regulation. Implications of the findings and recommendations for future research were discussed.
Keywords: Social competence; Parents' personality; Parent-child relationship; Young children